(untitled) (Research, Society and Development, 2021)
The terra firme forests, in some regions of the eastern Amazon, as well as in igapós and floodplains, present a high diversity of species. These forest types have different characteristics that result from the different influences of environmental factors. The work was carried out on the Pioneira farm belonging to Companhia Siderúrgica do Pará between latitudes of 5º 35’ and 5º 55’ (S) and longitude of 48º 50’ and 49º (W), located in the municipality of Marabá in the state of Pará. It has a total area of ​​4401.72 ha and its exploration is carried out in 12 plots of an average area of ​​199.38 ha per plot. To meet the objectives of this work, 100 trees were selected and cubed, following the balancing criterion within the diametrical occurrence classes. Each tree was sectioned every 2 meters, measuring the initial and final diameters of each 2-meter log and the tip, if applicable. From these data, using the SAEG statistical software, several regression models were tested, aiming to obtain precise volume equations for the forest. The equations that best fit the criteria used were models number 6, 9, 10 and 11, however equation 9, was the most suitable for presenting better results.